The Effect of OBS Studio Learning Media on the Learning Achievement of Class X Economics Students at Mahmudiyyah Senior High School - Maulida, Wahda; Retnawati, Saptina (International Journal of Economics Education Research (IJEER), 2022)
This study used a quantitative approach with a quasi-experimental type of research using the Nonequivalent Control Group Design which aims to determine the effect of the OBS Studio learning media on the learning achievement of class X economics during the Covid-19 pandemic. The variables in this study consisted of variables related to learning achievement (Y), and learning media variables (X). The population in this study were students of class X majoring in Economics with a total of 75 students consisting of 36 students in the experimental class and 39 students in the control class. Sampling technique with the type of probability sampling. The data analysis methods used are: validity and reliability test, descriptive analysis, classical assumption test of normality and homogeneity, one sample t test analysis, one binomial sample and independent sample t test. The results of the analysis showed that: (1) OBS Studio (Open Broadcaster Software) learning media in economics subjects was shown by the coefficient value of 81.46 and the value of sig 0.217 > sig value of 0.05 (5 %), which means H0 was rejected , and H1 was accepted. (2) the learning achievement of class X economics was shown by the coefficient value of the exact sig (1-tailed) value of 0.436 > 0.05, then H1 was accepted, namely the classical completeness of student learning achievement in economics class X exceeded 75 % (3) the effect of using OBS Studio learning media on the learning achievement of class X students in the economics subject was shown by the coefficient value of Group Statistics and the achievement of the Control class was 79.25 and the Experiment class was 81.46. The results of this study indicated that: (1) the average score class X economics class after being taught with Open Broadcaster Software learning media was higher than the KKM. (2) Classical completeness in the experimental class learning achievement exceeds 75%. (3) There was a significant difference between the economics learning achievement of class X experimental and class X control